Effect of oscillatory flow conditions on crystalliser fouling investigated through non-invasive imaging. (28th April 2022) - Sheridan, Rachel; Cardona, Javier; Tachtatzis, Christos; Chen, Yi-Chieh; Cleary, Alison; Briggs, Naomi; Florence, Alastair; Atkinson, Robert; Michie, Craig; Andonovic, Ivan; Sefcik, Jan
Highlights: Oscillatory flow conditions dictate fouling induction times and nucleation kinetics. High oscillatory Reynolds numbers promote fluid shear, leading to fouling. A non-invasive imaging method can provide timely early warnings of fouling. Abstract: Conditions that lead to undesired fouling events in oscillatory flow crystallisers are investigated. The moving fluid oscillatory baffled crystalliser is used to mimic the operating conditions of continuous oscillatory baffled crystallisers, while reducing materials and energy consumption. A non-invasive imaging method is deployed to determine fouling induction times as a function of oscillatory flow conditions and supersaturation in crystallisation of glycine and L-glutamic acid from aqueous solutions. Heterogeneous nucleation kinetics are extracted from the distribution of fouling induction times, showing that higher fouling nucleation rates are observed when the frequency and amplitude of the oscillatory flow are increased. Higher oscillatory Reynolds numbers result in increased fluid shear in the crystalliser, promoting heterogeneous nucleation at the glass-solution interface and leading to subsequent fouling. It is therefore essential to consider the dependence of fouling kinetics on operating conditions to enable rational design of continuous crystallisers that ensure smooth and robust operation.